1986-1991 (Ha Noi, 1992)
Sách thống kê kinh tế và thương mại Việt Nam 1986-1991
Keywords: Vietnam,Vietnam,Việt Nam,Việt Nam; Economics,Statistics,Commerce,Statistics,Kinh tế học,Thống kê,Thương mại,Thống kê